Historians on History and Tragedy - Juchnevičienė, Nijolė (Literatūra, 2015)
One of the distinct features of Greek historical thought – if are inclined to accept the existence of one in classical Greek culture and do not condemn it as totally unhistorical – is that it was greatly influenced by the poetry and was expressed primarily in poetry. The first historical dimension of man in Greek culture was poetical. When historiography came into existence, it, though very popular, has never become the central axis of Greek culture: this position steadily belonged to poetry, especially to epic and tragic poetry. Aristotle in his Poetics has already got the feel of similarity between the tragic poetry and historiography. He gave preference to tragic poetry as the best of literary means to record and to transfer the experience of the past. The other genres remained on the periphery of his field of vision; historiography in his opinion is not distinguished from the chronicle. Poetry is much better than history, because it deals with universal, history with the particular events. Thus according to Aristotle the connection between drama and history lies primarily in their subject matter; history is the source for plot and characters for both of them. But the most significant is not the similarity of the plot, but the affinity between historical thinking and dramatic thinking, namely, according to R. Collingwood, the concern of both the inner as well as the outer side of action. Aristotle was the first to compare tragedy and history. With the Aristotelian Peripatos some scholars were inclined to connect a special school of history, the so called tragic history. It has been alleged, that peripatetic theory of historiography deliberately applied to history-writing some of the principles, which Aristotle applied to tragedy. The evidence for a separate theory of tragic historiography is very doubtful indeed. But this topic, started by Aristotle, has become t^poV koin^V in post-Aristotelian historiography. Polybius, Plutarch, Lucian formulated their theory of historiography in sharp contrast to Hellenistic practice of neglecting the truth. The aim of history and its real value, accordind to them, can not be separated from the truth, whereas tragedy can not be separated from the deception. Polybius had the Stoic’s dislike of both rhetorical devices and emotional appeal. Hence he draws the sharp line between history and tragedy, between historical truth and malicious fiction, yeÒdoV. Plutarch is very peremptory in his statements, but his practice contradicts his theory. Lucian clearly distinguishes history from rhetoric, establishes it as a separate genre by contrasting it with tragedy.